2009
DOI: 10.1111/j.1758-2229.2009.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal changes in the genetic diversity in French bloom‐forming populations of the toxic cyanobacterium, Microcystis aeruginosa

Abstract: Microcystis aeruginosa is a toxic cyanobacterium, which is able to bloom in a wide range of freshwater ecosystems. By sequencing the Internal Transcribed Spacer (ITS) of the ribosomal operon, we compared the genetic composition of several French bloom-forming M. aeruginosa populations from two reservoirs located on the Loire River, at two sampling points located between these reservoirs, and finally in two ponds closely linked to this river. No significant difference was found in the genetic diversity of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
66
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 50 publications
9
66
3
1
Order By: Relevance
“…Considerable studies have been performed on the genotypic composition of Microcystis blooms. Recent developments in elucidating the genetic diversity of Microcystis blooms by sequencing the environmental rRNA genes, such as internal transcribed spacer (ITS), have provided new insight into the genetic diversity of Microcystis populations in freshwaters [1,2,15]. Briand et al [2] obtained 306 different genotypes from 784 ITS sequences in a France reservoir.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable studies have been performed on the genotypic composition of Microcystis blooms. Recent developments in elucidating the genetic diversity of Microcystis blooms by sequencing the environmental rRNA genes, such as internal transcribed spacer (ITS), have provided new insight into the genetic diversity of Microcystis populations in freshwaters [1,2,15]. Briand et al [2] obtained 306 different genotypes from 784 ITS sequences in a France reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that marked changes occurred in the ITS genotype composition of M. aeruginosa populations during the development of the bloom. Sabart et al [15] compared the genetic composition of several French bloom-forming Microcystis populations from different water systems along the Loire river. They obtained a total of 379 ITS genotypes among 950 ITS sequences.…”
Section: Introductionmentioning
confidence: 99%
“…This finding added a better understanding the spatiotemporal dynamics of cyanobacterial blooms dominated by filamentous cyanobacteria in freshwater ecosystems. Comparative results from ITS sequences between Microcystis and Dolichospermum blooms in Lake Taihu, demonstrated that genetic diversity (represented as values of genotype number/ITS sequence number) from Microcystis blooms was higher than that from Dolichospermum blooms (Bozarth et al, 2010;Sabart et al, 2009). These studies on genotypes of Microcystis dominated blooms, from river-based reservoirs with large surface areas and certain degrees of water flow and pond systems, indicated that strong hydrodynamics influence may trigger the selection of the main genotypes.…”
Section: Discussionmentioning
confidence: 85%
“…Our study corroborates this result since both these parameters differed between the different sampling sites we prospected in Grangent reservoir in 2009. Associated to the dynamics resulting from growth and decay, horizontal heterogeneity was hence supposed to be one of the main drivers of the high temporal variability of toxic potential and genotypic structure that were frequently reported in blooms of M. aeruginosa [4,8,22,23,25,26,38,39]. Now, the vertical heterogeneity we observed through this study represents a third part to consider in order to fully understanding the temporal dynamics of genetic diversity and toxin production in M. aeruginosa's blooms.…”
Section: Discussionmentioning
confidence: 96%
“…Many comprehensive studies have therefore been realized in order to explain the ecological success of this cyanobacterium and to unravel the complex set of factors driving both its dynamics and its toxicity. Such previous studies mainly dealt with the genetic diversity of M. aeruginosa's populations [4][5][6][7], the toxic potential of M. aeruginosa [8][9][10][11][12], and the determinism of the different steps of M. aeruginosa's life cycle [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%